Resistance training status and effectiveness of low-frequency resistance training on upper-body strength and power in highly trained soccer players - Hertzog, M.; Rumpf, M. C.; Hader, K. (The Journal of Strength and Conditioning Research, 2020)
Soccer is classified as a contact/collision sport with many player-to-player duels. Winning these duels, shielding the ball or fending off an opponent requires upper-body strength and power. Therefore, this study aimed (a) to examine the time-related effect of an upper-body resistance training (RT) on maximal strength and power changes in highly trained soccer players and (b) to investigate if the RT status influences these changes throughout a competitive season. Twenty-eight soccer players participated in this study and were divided into an untrained group (UG) and a trained group (TG), according to their RT status. Both groups performed the same upper-body RT once a week, over 30 weeks. Maximal strength (1 repetition maximum [1RM]) and maximal power (MP) were assessed before, during, and after the competitive season. Both groups significantly improved 1RM and MP over the entire competitive season, with a moderate (TG, 13%) to very large (UG, 21%) magnitude in 1RM and with a small (TG, 8%) to moderate (UG, 13%) magnitude in MP. After the initial 10 weeks of RT, UG presented significant and slightly (1RM) to moderately (MP) greater improvements than TG. For all other time intervals, the between-groups' changes in 1RM were rated as similar. For the last 20 weeks of the RT, the change in MP was significantly lower for UG compared with TG. One upper-body RT session per week will provide sufficient stimulus to enable an almost certain improvement in strength and power throughout a competitive season for all players disregarding their initial RT status.